Concussion Treatment Using Massage Techniques: a Case Study - M.Ed., LMP, Sylvia L. Burns (International Journal of Therapeutic Massage & Bodywork, 2015)
Background: Concussion, its recognition, diagnosis, and treatment is a growing public health issue. Massage practitioners who specialize in rehabilitation deal with a variety of injury cases that involve concussion, including those incurred by falls, motor vehicle incidents, and sports injuries. Purpose: This case study presents a unique massage therapy approach to concussion trauma treatment. Participant: Male 23-year-old intramural soccer player diagnosed with postconcussion syndrome resulting from a fall. Intervention: Assessment and treatment were completed in two sessions of 45 minutes spaced two days apart. Massage therapy techniques were applied to injury areas by a Licensed Massage Practitioner. Results: Using the Balance Error Scoring System (BESS) and self-report, the outcome measures showed diminished concussion symptoms and regained ease in range of motion in the cervical area. Conclusion: Positive results for this case highlight the potential importance of massage therapy work to reduce headache, dizziness, and nausea in concussion recovery. In the presence of such outcomes, massage therapy may also have a supportive role in a person’s return to function after concussion.